Caracterização morfológica para estudo da divergência genética de híbridos interespecíficos de pitaya - da Silva, Adriana de Castro Correia; Sabião, Rafael Roveri [UNESP]; Chiamolera, Fernando Marcelo [UNESP]; Segantini, Daniela Mota [UNESP]; Martins, Antonio Baldo Geraldo [UNESP] (FapUNIFESP (SciELO), 2017)
With recent cultivation in Brazil, the dragon fruit still have lacks related to the selection of promising materials and there are not yet commercial varieties in the country. Therefore, manual pollination cross were held in 2010, between plants of H. undatus x H. polyrhizus and H. undatus x H. setaceus. Aiming evaluate the genetic diversity of the progenies for future use in breeding program, based on cladodes characteristics, six characters were assessed: length and diameter of stem, distance between areoles, arch height, number and size of spines/areole. From the Euclidean distance matrix analysis was constructed a dendrogram by the UPGMA method. There was great variability among hybrids, and eight of them have shown promise for use in breeding program.
Morphological traits as tool to verify genetic variability of interspecific dragon fruit hybrids
Keywords: Genetic relationship; H. polyrhizus; H. setaceus; Hylocereus undatus; Multivariate analysis